Analysis of Ecotourism and Creative Economy on Welfare People at Sulfur Springs Baths In the East Kaduara of Sumenep - Wadhan W (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This research aims to analyze the influence of ecotourism (X1) and creative economy (X2) on community welfare (Y). and calculate how much influence ecotourism (X1) and the creative economy (X2) have on community welfare (Y). This research is research descriptive quantitative. Based on the results of research conducted regarding the influence of ecotourism (X1), creative economy (X2) on community welfare (Y), the significance value of the ecotourism variable (X1) is 0.027, where this figure is smaller than 0.05. This shows that the ecotourism variable (X1) has an influence on the community welfare variable. The significance value of the creative economy variable (X2) is 0.002, which is smaller than 0.05. This shows that the creative economy variable (X2) has an influence on the community welfare variable. while the calculated F is 9.086 while the resulting significance value is 0.000 which is smaller than 0.05. independent variables which include ecotourism (X1) and creative economy (X2) have a simultaneous influence on the dependent variable (community welfare/ Y). This means that ecotourism (X1) and the creative economy (X2) have a joint (simultaneous) effect on community welfare (Y).